PENGARUH PERCEIVED VALUE AND PERCEIVED QUALITY TERHADAP KEPERCAYAAN KONSUMEN DI RUMAH SAKIT KARTIKA SARI - Glory Budi Dharma (Jurnal Manajemen dan Pemasaran Jasa, 2012)
The background of this research was consumer loyalty has become one of the principal lines of research in marketing. Some authors consider that studies oriented towards the analysis of perceived quality and satisfaction make sense in the framework of the explanation of purchasing loyalty, because customer loyalty has become the principal objective of firms.The objective (s) of this research was identifying the effect perceived value and perceived quality toward consumer’s trust honesty and consumer’s trust benevolence. The design of this research applies hypothesis testing to examine all hypotheses in this study. The method used in this study is multiple regressions between independent variables and dependent variable. Data analysis used in this research was collected by distributing questionnaires which were distributed on 110 respondents at Kartika Sari Hospital. There were 107 responses of which 100 completed and usable for analyzed by multiple regressions. The result of this research conclude that the professionalism, perceived quality, value monetary costs, value non monetary costs have positive and significant impact on consumer’s trust honesty dan consumer’s trust benevolence.Keywords : Sonsumer loyalty, Perceived value, Perceived quality, Satisfaction